2020
DOI: 10.1161/circresaha.119.316424
|View full text |Cite
|
Sign up to set email alerts
|

LDL Receptor Regulates the Reverse Transport of Macrophage-Derived Unesterified Cholesterol via Concerted Action of the HDL-LDL Axis

Abstract: Rationale: The HDL-mediated stimulation of cellular cholesterol efflux initiates the reverse cholesterol pathway from macrophages (m-RCT), which ends in the fecal excretion of macrophage-derived unesterified cholesterol (UC). Early studies established that LDL particles could act as efficient intermediate acceptors of cellular-derived UC, thereby preventing the saturation of HDL particles and facilitating their cholesterol efflux capacity (CEC). However, the capacity of LDL to act as a plasma chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 52 publications
3
43
0
Order By: Relevance
“…However, cholesterol efflux is only the first step of the overall process, and, importantly, macrophage-specific reverse cholesterol transport to feces in vivo (m-RCT) was impaired in NAM HD-treated ApoE-deficient mice [ 61 ]. Therefore, delayed plasma clearance of non-HDL might underlie defective m-RCT [ 61 ], as observed in LDL receptor knockout mice [ 69 ]. Overall, the detrimental effect of NAM HD treatment on m-RCT, in the context of a concomitantly severely worsening hyperlipidemia, highlights the antiatherogenic power of this compound at least in mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, cholesterol efflux is only the first step of the overall process, and, importantly, macrophage-specific reverse cholesterol transport to feces in vivo (m-RCT) was impaired in NAM HD-treated ApoE-deficient mice [ 61 ]. Therefore, delayed plasma clearance of non-HDL might underlie defective m-RCT [ 61 ], as observed in LDL receptor knockout mice [ 69 ]. Overall, the detrimental effect of NAM HD treatment on m-RCT, in the context of a concomitantly severely worsening hyperlipidemia, highlights the antiatherogenic power of this compound at least in mice.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism could be related to oxidized LDL (34,37). Work in experimental animals interestingly suggests that lack of functional hepatic LDLRs attenuate RCT via concerted action of the HDL-LDL-axis (38). Regardless of the mechanism, findings in adolescent FH subjects support that HDL function is altered early in life (39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that LDL can induce cholesterol efflux from cultured macrophage foam cells via the ABCA1 transporter 49 . In our experimental setting we may exclude the contribution of LDL to cholesterol efflux since CEC studies have been performed by incubating cells with the serum fraction containing only HDL.…”
Section: Cholesterol Efflux Capacity and Sex Hormonesmentioning
confidence: 99%